State regulation and coordination of Ukraine’s participation in international aerospace organizations - Psiuk M.О. (Економіка, управління та адміністрування)
Today, the aerospace industry is one of the leading industries, the successful development of which provides technological, economic and political leadership of Ukraine on the world stage. It is noted that Ukraine’s aerospace activities are focused primarily on expanding and deepening international cooperation at the interstate, intergovernmental and interdepartmental levels, on the development of foreign economic activity of space enterprises, bringing national space developments to the world market, introduction of advanced space technologies in various fields of economy, creating conditions for the development of competition and private initiative. The article analyzes Ukraine’s participation in the work of leading international organizations in the field of regulation, coordination and use of space and space technologies. The author substantiates the necessity of state support in the development and implementation of international cooperation projects and cooperation programs, which is one of the main directions of state regulation of the aerospace industry of Ukraine.